Influence Of Neck Slaughtering In Broiler Chicken Meat On Physicochemical Analysis And Metabolites 'fingerprinting' To Enhance Meat Quality - Shikh Mohd Shahrul Nizan Shikh Zahari; Dzulfadli Rosli; Mohd Nazmi Abd Manap; Nurfatin SyahirahMohamed Ali; Atiqah Ruqayyah Zabidi; Nazariyah Yahaya (Elsevier, 2024)
Indexed by WOS/Scopus/ERA